Effect of cytoplasmic male sterility type on chlorophyll content in leaves of grain sorghum hybrids - O. P. Kibalnik; L. A. Elkonin (Вавиловский журнал генетики и селекции)
New types of CMS-inducing cytoplasms cannot be applied to hybrid sorghum breeding without knowledge of their effects on major biological and commercial plant traits. In our studies of F1 hybrids obtained by crossing of two sets of isonuclear CMS lines (with nuclear genomes of cv. Pishchevoye 614 (P614) and Zhelyozyornoye 10 (Zh10)) to two pollen parents (cv. Pishchevoye 35 (P35) and Mercury), we focused our attention on the effects of A3, A4, 9E, and M35-1A cytoplasms on chlorophyll content at different developmental stages of sorghum plants. It was found that hybrids with different types of male-sterile cytoplasm differed in chlorophyll content, and the genotypes of the CMS line and the pollen parent influenced the manifestation of cytoplasmic differences. In the F1 hybrids obtained with CMS lines possessing the P614 genome, sterile M35-1A cytoplasm increased chlorophyll a content, in comparison to 9E cytoplasm. In the F1 hybrids obtained with CMS lines with the Zh10 genome and the P35 pollen parent, sterile A4 cytoplasm increased the sum of chlorophyll a and b, in comparison to A3 and 9E cytoplasms, whereas no differences were recorded in the F1 hybrids obtained with Mercury. The F1 hybrids obtained with CMS lines with the P614 genome showed heterosis for total chlorophyll content at the tillering stage. Overdominance of this trait was observed in hybrids with M35-1A cytoplasm; true heterosis exceeded analogous indices in 9E cytoplasm by 19.0 %, and the hypothetical heterosis, by 20.6 %. These data demonstrate that the application of new types of CMS-inducing cytoplasms allows raise of F1 hybrids with heterosis for chlorophyll content. Thus, such types can be used to increase hybrid productivity.